ANALYSIS OF INTERNAL AND EXTERNAL FACTORS AFFECTING THE SUSTAINABLE DEVELOPMENT OF SMALL BUSINESS ENTITIES - M. M. Dadaboyeva (Ecominds Press, 2025)
This article analyzes the key internal and external factors influencing the sustainable development of small business entities. Internal factors such as the level of management, financial resources, innovation potential, and human capital of the enterprise are examined. External factors are studied within the framework of the economic environment, legislative base, competitive climate, and state support policies. The article also presents existing problems and proposes solutions. Based on statistical data from Uzbekistan, an analysis is conducted, and the necessity of a comprehensive approach in ensuring the sustainability of small businesses is substantiated.
Keywords: Uzbekistan’s economy, small business, sustainable development, internal factors, external factors, entrepreneurship, economic environment, state support, competitiveness.